Increased AOC1 Expression Promotes Cancer Progression in Colorectal Cancer - Liu, Fangyuan; Ou, Weijun; Tang, Wenbo; Huang, Zhenyu; Zhu, Zhehui; Ding, Wenjun; Fu, Jihong; Zhu, Yilian; Liu, Chenying; Xu, Weimin; Du, Peng (Frontiers in Oncology, 2021)
Background: Amine oxidase copper containing 1 (AOC1) is a gene whose biological function in colorectal cancer (CRC) has not been elucidated. Therefore, the purpose of this study was to investigate the clinical significance of AOC1 expression in CRC and its biological function in CRC cell lines. Materials and Methods: AOC1 expression levels were examined in paired CRC and peritumoral tissues, and distant liver metastatic tissues were examined using quantitative real-time PCR, western blotting, and immunohistochemistry staining. The log-rank test and Cox regression model were used to analyze the relationship between AOC1 expression and prognosis. Proliferation assays (Cell Counting Kit‐8 and colony formation assays) and migration assays (Transwell and wound healing assays) were performed to assess the biological role of AOC1 in CRC cells. Results: AOC1 expression significantly increased in human CRC tissues, especially in liver metastases, and was associated with a worse prognosis. In addition, AOC1 had higher expression in tumor organoids than in normal organoids, suggesting that it was highly expressed in the tumor epithelium. Functional analysis demonstrated that AOC1 knockdown inhibited the proliferation and migration of CRC cells in vitro. Conclusion: High expression of AOC1 was significantly associated with worse clinical outcomes, was an independent risk factor for poor prognosis, and promoted aggressive CRC cell phenotypes. AOC1 is expected to become a novel biomarker for predicting the prognosis of patients with CRC and an effective therapeutic target in clinical practice.